Controlling bromate formation in the Co(II)/peroxymonosulfate process by ammonia, chlorine-ammonia and ammonia-chlorine pretreatment strategies. (1st August 2018) - Ling, Li; Li, Zhaobing; Fang, Jingyun; Shang, Chii
Abstract: The Co(II)/peroxymonosulfate (Co(II)/PMS) process, producing sulfate radicals (SO4 - ), effectively removes organic pollutants in water, while producing a significant amount of bromate (BrO3 − ) in the presence of bromide (Br − ). This paper investigates the ammonia (NH3 ) addition, chlorine-ammonia (Cl2 -NH3 ) and ammonia-chlorine (NH3 -Cl2 ) pretreatment strategies in controlling BrO3 − formation in 20 min in the Co(II)/PMS process at pH 4.0. The addition of NH3 retarded the BrO3 − formation, but only at a reduction level of about 9.5% for NH3 concentration of 50 μM, and was mainly attributed to the protonation of NH3 at pH 4 (99.99% as NH4 +, did not react with HOBr). Both the Cl2 -NH3 and NH3 -Cl2 pretreatment strategies at HOCl and NH3 dosages of 15 and 50 μM, respectively, reduced 95% or more of the overall BrO3 − formation and retarded the BrO3 − formation, with the NH3 -Cl2 pretreatment strategy outperforming Cl2 -NH3 . The reduction of the BrO3 − formation was mainly attributed to the formation of monochloramine (NH2 Cl) in both pretreatment strategies. NH2 Cl effectively outcompetes SO4 - to react with HOBr and forms NHBrCl, with the apparent reaction rate constant between NH2 Cl and HOBr more than 100 times faster than that between SO4 - and HOBr. However, the oxidation/degradation of NHBrCl in the Co(II)/PMS process reforms HOBr, and, although less in quantity, is oxidized to BrO3 − at higher Co(II) and Br − concentrations. Thus, the NH3 -Cl2 and Cl2 -NH3 pretreatment strategies inhibit the BrO3 − formation more significantly at lower Co(II) and Br − concentrations. In all cases, the generation of SO4 - in 20 min was not affected by the implementation of the three BrO3 − pretreatment strategies. Graphical abstract: Highlights: Inhibition of BrO3 − formation at pH 4.0 followed the order: NH3 -Cl2 >Cl2 -NH3 >NH3 . At pH 4, NH3 is primarily in the form of NH4 + with less reactivity towards HOBr. NH2 Cl formed in NH3 -Cl2 and Cl2 -NH3 processes outcompeted SO4 . - in quenching HOBr. NH3 -Cl2 process formed more NH2 Cl and performed better than Cl2 -NH3 process. NH3 -Cl2 and Cl2 -NH3 processes worked better at lower Co(II) and Br − concentrations.